2009
DOI: 10.1002/em.20447
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction by sulfur‐containing compounds in malignant and nonmalignant human cells

Abstract: Plants have traditionally represented a main source for the discovery of many biologically active substances with therapeutic values. Sulfur-containing compounds exhibit pleiotropic biological effects supporting their potential use in multitargeted cancer prevention and treatment. As potential anti-cancer agents, they have been shown to inhibit or retard the growth of various cancer cells in culture and implanted tumors in vivo. The compounds significantly inhibit experimental tumorigenesis in a wide range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 143 publications
(186 reference statements)
3
13
0
Order By: Relevance
“…As revealed by several studies, DAS, DADS, DATS, and ajoene reduced viability of human malignant cells (neuroblastoma cells, prostate cancer cells, lung tumor cells, and leukemia cells) without affecting viability of human normal cells (human primary neurons, normal prostate epithelia cells, normal lung fibroblasts, and healthy mononuclear blood cells) [115][116][117][118]. Both BITC and AITC support this evidence, showing inhibition of breast cancer cell survival and minimal effects on healthy breast cell survival [1].…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…As revealed by several studies, DAS, DADS, DATS, and ajoene reduced viability of human malignant cells (neuroblastoma cells, prostate cancer cells, lung tumor cells, and leukemia cells) without affecting viability of human normal cells (human primary neurons, normal prostate epithelia cells, normal lung fibroblasts, and healthy mononuclear blood cells) [115][116][117][118]. Both BITC and AITC support this evidence, showing inhibition of breast cancer cell survival and minimal effects on healthy breast cell survival [1].…”
Section: Resultssupporting
confidence: 57%
“…Furthermore, ITCs are able to oxidize a member of the Trx-dependent antioxidant system, namely peroxiredoxin (Prx), which exists in mammalian cells in six different forms at least. PEITC (15 μM) and SFN (60 μM) rapidly and selectively oxidize the mitochondrial Prx3, but not the cytosolic Prx1 and Prx2, which are not oxidized under the same conditions [1,101]. Increased levels of ROS are reported after SFN treatment (5-20 μM) of p53-null MG63 osteosarcoma cells [104] and PEITC and BITC treatment of U-2 OS cells (10 μM and 7.5 μM, respectively) [100].…”
Section: Ros Generationmentioning
confidence: 89%
See 2 more Smart Citations
“…We were intrigued by Jaridonin's anticancer profile to make use of its special scaffold as an introductory template to synthesize novel Jaridonin derivatives to develop effective and safe anticancer agents. Numerous studies have identified sulfur-containing compounds possess multiple biological effects supporting their potential use in multi-targeted cancer prevention and treatment [20]. And recently, expeditious synthetic methods that were based on the Jaridonin scaffold were successfully built by our group to access a series of disulfide bond-substituted derivatives with improved anticancer activity, among them, DS2 (the synthesis and the structure identification of DS2 are shown in Supplementary Figures S1, S2 and S3) suggesting that disulfide bond-substituted modifications seem to be tolerated for producing biologically interesting molecules.…”
Section: Introductionmentioning
confidence: 99%